Clinical-diagnostic value of the method of microbial markers mass spectrometry in patients with recurrent chronic pharyngitis - I. A. Snimshikova; B. V. Agafonov; A. V. Simonova; V. V. Pchelyakova; A. V. Gostry (Лечащий Врач, 2021)
The article covers the new method of diagnostics — microbial markers mass spectrometry in chronic pharyngitis (CPH) with recurrent course. This method is based on quantitative definition of microorganism markers: fatty acids, aldehydes, alcohols and sterols directly in the clinical material (throat smears) in CPH. The technology allows to define, by the level of microbial markers, concentration of 57 microorganisms in the clinical material, within 3 hours after it gets to the laboratory.